Aspek Yang Berpengaruh Pada Manajemen Strategi Organisasi Non Profit(Studi Manajemen Strategi Pada Pemerintah Kota Cilegon) - Nurbaity, Nurbaity; Sartika, Ratu; Suhendra, Suhendra; Ilham Maliki, Budi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Strategic Management has significant role for Cilegon City governmental organization in order to improve public service quality. In the local autonomy era all the organizations are needed to be able to make appropriate policies to anticipate environment change and to fulfill public demand of qualified service. This research is focus on factor that affect process of that strategic management. This research proposed three variables, which are power, leadership, and commitment. As “explanatory reseach” this research intended to explain some problems which formulated as follow: (a) Does power influences to strategic management at Cilegon Citygovernmental organization? (b) Does leadership influences to strategic management at Cilegon Citygovernmental organization? (c) Does commitment influences to strategic management at Cilegon Citygovernmental organization? By opposing strategic management into three dimensions: formulation, implementation, and evaluation, the analyse is used “Structural Equation Modelling” (SEM) was very suitable because there were two analysis stages (Second Order Confirmatory). Despite, it was desired contribution of the three dimensions of management would be studied. The respondents are 110 persons representing all the kind of Cilegon City governmental organization: departement (dinas), committee (badan), and office. The conclusions of the result study are: a) the power and leadership negatively affected strategic management. There were because of bureaucratic-centralistic power and directive leadership, (b) the commitment affected strategic management, especially on implementation stage, (c) the leader can’t maximaize transforming existing power for success of strategic management, (d) the strategic management can’t maximize improving public service as the bureaucartic- centralistic power and directive leadership.